2020
DOI: 10.1049/mnl.2019.0621
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced conductivity of anatase TiO 2 nanowires by La and Co co‐doping

Abstract: In this work, the conductivity of anatase titanium dioxide (TiO 2) nanowires was enhanced by lanthanum (La) and cobalt (Co) co-doping method. The nanowires were synthesised via a facile solvothermal process. The diameter of as-synthesised nanowires is about 300 nm and length more than 20 μm. The electrical properties were studied based on single nanowire field-effect transistor; the anatase TiO 2 nanowires exhibit n-type conductivity with mobility of 2.18 cm 2 V −1 S −1 and carrier concentration of 1.95 × 10 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Element doping is an effective strategy to improve the electrical conductivity of host scaffolds, which can further enhance its charge collection ability. [121][122][123] The more efficient collection of the photogenerated carriers in the photoanodes can be indicated [79] Copyright 2014, Elsevier Ltd. ZnO/Fe 2 O 3 core/shell NWs: b) TEM image; c) LSV plots. b,c) Reproduced with permission.…”
Section: Optimization Of Conductive Host Scaffoldsmentioning
confidence: 99%
“…Element doping is an effective strategy to improve the electrical conductivity of host scaffolds, which can further enhance its charge collection ability. [121][122][123] The more efficient collection of the photogenerated carriers in the photoanodes can be indicated [79] Copyright 2014, Elsevier Ltd. ZnO/Fe 2 O 3 core/shell NWs: b) TEM image; c) LSV plots. b,c) Reproduced with permission.…”
Section: Optimization Of Conductive Host Scaffoldsmentioning
confidence: 99%
“…Recent studies have shown that transition metal (TM) [15][16][17][18][19] and non-metal atoms doping [20][21][22][23] are a feasible and efficient way to enhance the photocatalytic performance of TiO 2 . Nevertheless, the TM doping is deemed unstable and can introduce localized impurity states, which increase the recombination rate of photo-generated electron-hole pairs.…”
Section: Introductionmentioning
confidence: 99%
“…In the 19th century, semiconductor materials [5, 6] have played an extremely important role in the development of photocatalytic technology. Among them, TiO 2 [7, 8] is a representative semiconductor material. It has been widely used in photocatalysis technology because of the high chemical stability, non‐toxicity and strong photo‐oxidative degradation on the OCs.…”
Section: Introductionmentioning
confidence: 99%